2021
DOI: 10.1002/advs.202102924
|View full text |Cite
|
Sign up to set email alerts
|

2D Material‐Based Optical Biosensor: Status and Prospect

Abstract: The combination of 2D materials and optical biosensors has become a hot research topic in recent years. Graphene, transition metal dichalcogenides, black phosphorus, MXenes, and other 2D materials (metal oxides and degenerate semiconductors) have unique optical properties and play a unique role in the detection of different biomolecules. Through the modification of 2D materials, optical biosensor has the advantages that traditional sensors (such as electrical sensing) do not have, and the sensitivity and detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(62 citation statements)
references
References 214 publications
(408 reference statements)
0
54
0
Order By: Relevance
“…Moreover, the internal light-to-heat conversion efficiency of MXene, more specifically Ti 3 C 2 , was measured to be 100%, demonstrating a flawless energy conversion [ 181 ]. Nevertheless, to further enhance MXenes applications, several optical-associated qualities such as plasmonic, luminescence efficiency, and nonlinear optical properties must be unraveled [ 178 – 181 , 184 ].…”
Section: Mxene: Synthesis and Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the internal light-to-heat conversion efficiency of MXene, more specifically Ti 3 C 2 , was measured to be 100%, demonstrating a flawless energy conversion [ 181 ]. Nevertheless, to further enhance MXenes applications, several optical-associated qualities such as plasmonic, luminescence efficiency, and nonlinear optical properties must be unraveled [ 178 – 181 , 184 ].…”
Section: Mxene: Synthesis and Propertiesmentioning
confidence: 99%
“…The studies on thermal conductivities in terms of thermal expansion coefficients of MXenes are still sparse, despite their importance for electrical and energy-related heat dissipation devices [ 155 ]. Simulation studies indicated low thermal expansion coefficients [ 37 , 184 , 185 ] and superior heat conductivities of MXene-based materials than phosphorene and MoS 2 monolayer [ 184 , 186 , 187 ]. It was observed that the thermal conductivities of oxygen–terminated compounds rise with the metal “M” atomic number [ 119 , 184 ].…”
Section: Mxene: Synthesis and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The field of biosensors is highly dynamic, with scientific research advances that have mainly flourished in the last decades. Numerous biosensors have been developed for nanotechnology, engineering, molecular biology, computer, and optics [ 1 ]. In general, there are three types of biosensors: electrochemical, optical, and piezoelectric; each kind has its own method for transducing signals [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high interacting field leads to a high sensitivity. Over the years, various photonic structures have been proposed such as surface Plasmon polaritons (SPPs) [ 17 , 18 ], 2D materials [ 19 , 20 ], long period gratings (LPGs) [ 21 , 22 ], multimode interferences [ 23 ], ring resonators [ 24 , 25 ], Bragg gratings [ 26 , 27 , 28 , 29 , 30 , 31 ], etc. The performance of the structures based on LPGs, SPPs, multimode interferometers, and ring resonators is often limited by broad bandwidth, a bulky setup, or a free spectral range.…”
Section: Introductionmentioning
confidence: 99%